Photocatalytic Degradation of Methylene Blue Using TiO2 Impregnated Diatomite - Ranfang Zuo; Gaoxiang Du; Weiwei Zhang; Lianhua Liu; Yanming Liu; Lefu Mei; Zhaohui Li (Advances in Materials Science and Engineering)
Nano-TiO2 showed a good catalytic activity, but it is easy to agglomerate, resulting in the reduction or even complete loss of photocatalytic activity. The dispersion of TiO2 particles on porous materials was a potential solution to this problem. Diatomite has high specific surface and absorbability because of its particular shell structure. Thus, TiO2/diatomite composite, prepared by loading TiO2 on the surface of diatomite, was a good photocatalyst, through absorbing organic compounds with diatomite and degrading them with TiO2. Scanning electron microscopy (SEM), energy dispersive spectrum (EDS), X-ray diffraction (XRD), chemical analysis, and Fourier transform infrared spectrometry (FTIR) indicated that TiO2 was impregnated well on the surface of diatomite. Furthermore, TiO2/diatomite was more active than nano-TiO2 for the degradation of methylene blue (MB) in solution. MB at concentrations of 15 and 35 ppm can be completely degraded in 20 and 40 min, respectively.